Peran Pelestarian Tenun Tradisional dalam Membentuk Identitas Budaya Masyarakat Pringgasela Lombok Timur - Eka Mala Zurya Maulana; Zidni Zidni; Abdul Hafiz; Lalu Wahyu Andi Purnama; B. Fitri Rahmawati (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aims to examine the role of traditional weaving preservation in shaping the identity of the Pringgasela community, East Lombok. Pringgasela weaving serves not only as a craft product but also as a symbol of local identity passed down from generation to generation. In the context of modernization and globalization, weaving preservation is crucial for maintaining the sustainability of local cultural values. The research method used was descriptive qualitative with a case study approach in East Pringgasela Village. Data were collected through observation, in-depth interviews with weavers, traditional leaders, and the local community, as well as documentation of weaving preservation activities. The results of the study indicate that weaving preservation in Pringgasela plays a significant role in shaping and strengthening community identity. Weaving serves as a medium for cultural expression, strengthens social solidarity, and serves as an economic resource for the community. Conservation efforts include cultural education in schools, weaving training for the younger generation, the formation of the Nine Weaving Group (KNP), and the promotion of weaving as a superior regional product. Preservation is carried out through free weaving school programs, the use of natural dyes, and the revitalization of traditional motifs such as ragi sundawa, saritunggu, and pucuk rebung, which have existed since the 14th century AD. In conclusion, the preservation of traditional weaving in Pringgasela not only preserves cultural heritage but also shapes the community's collective identity amidst the changing times.